Audio Visual Education Effectivity to Increase Knowledge about Anemia in Pregnant Women - Iin Nuraeni; Elfira Sri Futriani Futriani; Farida Murtiani; Aninda Dinar Widiantari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: WHO reported 36.5% pregnant women in the world experienced anaemia, which 75.0% of them lived in developing countries. It included 63.5% of them who lived in Indonesia. The highest prevalence of anemic pregnancy in Jakarta province was located in North Jakarta, that related to iron deficiency and nutritional status. Boosting knowledge and educating women about pregnancy had to be done effectively in order to get optimal output. Choosing the right educational media was an essential part of the movement. Audio Visual Education (AVE) was commonly use to educate people, instead of limited resources. It stimulated two human sense, sight and hearing, which estimated could increase learning process. Method: We held a quasi-experimental study by gathering 30 pregnant women to watch AVE about anemia in pregnancy who were willing to participate and havent received any education about anemia via educational video. Exclusion criteria were being uncooperative, such as not watching the video completely and didn’t fill in pre- and posttest completely. We used purposive sampling to gather participants. There were pre and post-test ten minutes before and after intervention. We performed Wilcoxon Test to analyze the effectivity of AVE in order to increase knowledge about anemia (p<0.05). Results: We found AVE could boost knowledge score in the third pregnant women statistically significant. Before intervention, average knowledge score was 56,7% which increased to 91,7% after AVE (p value=0.0001).   Conclusion: This study implied AVE was an effective media to increase participant’s knowledge about anemic pregnancy in pregnant women. Strengthening health literacy through planned educational programs would improve health behavior of individual and community.